Is Europe back on track? Impetus from the German EU Presidency - Kurpas, Sebastian; Riecke, Henning (2007)
Abstract: Rarely has an EU Presidency been met with such high expectations as Germany’s in the first half of 2007. With hindsight, it might be said that these expectations have largely been fulfilled. The agreement on a detailed mandate for the upcoming Intergovernmental Conference (IGC) under the Portuguese Presidency now offers a way forward for a Union that has been ‘in crisis’ since the French and Dutch no-votes. This report offers an overview of the German Presidency’s aims in the various policy areas and makes an assessment of the achievements of its six-month term. A summary of the content and structural background of German EU policy is given, explaining developments since unification, Germany’s motivations for European integration, public opinion on European integration and the stances taken by the key political players in Germany. Insight into the organisational structures of the Presidency appears in the annex. While acknowledging the difficulty of gauging the exact impact of the